The Importance of Foreign Direct Investment to Empower Micro, Small and Medium Enterprises in Indonesia - Raden Ani Eko Wahyuni (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
This study discusses the importance of foreign direct investment (FDI) for the empowerment of micro, small and medium enterprises (MSMEs) in Indonesia. The method used in this study is a juridical approach method with analytical descriptive research specifications. This discussion in this study suggests that foreign investment, particularly FDI, plays an important role in the economy of a nation, as sources of skills, knowledge and technologies. In facing high competitions, MSMEs in Indonesia need to be able to face global challenges, such as increased product and service innovations, development of human resources and technology, and expansion of marketing areas. FDI, therefore, can play a crucial role to empower local MSMEs in Indonesia.